2023
DOI: 10.3390/jcm12062377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Coadministered Ezetimibe–Rosuvastatin plus Telmisartan in South Korean Patients with Dyslipidemia and Hypertension: A Multicenter, Randomized, Double-Blind, Active-Controlled, Phase III Trial

Abstract: Background: The introduction of a fixed-dose combination (FDC) is expected to improve treatment compliance. Methods: There were 181 subjects who were randomized to three groups: ezetimibe–rosuvastatin 10/20 mg + telmisartan 80 mg, ezetimibe–rosuvastatin 10/20 mg, and telmisartan 80 mg. The primary outcomes were change in mean sitting systolic blood pressure (MSSBP) and percentage change in low-density-lipoprotein cholesterol (LDL-C) compared to baseline at week 8. Results: The least-square mean (SE) in MSSBP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, a previous study showed that ezetimibe‐rosuvastatin with telmisartan therapy is effective and safe compared to either ezetimibe‐rosuvastatin double therapy or telmisartan monotherapy. 51 The triple combination yielded improvements in the primary endpoints of msSBP and LDL‐C levels compared to their respective control groups. The efficacy results were consistent with this study, and no clinically significant differences were observed in the safety outcomes in both studies.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a previous study showed that ezetimibe‐rosuvastatin with telmisartan therapy is effective and safe compared to either ezetimibe‐rosuvastatin double therapy or telmisartan monotherapy. 51 The triple combination yielded improvements in the primary endpoints of msSBP and LDL‐C levels compared to their respective control groups. The efficacy results were consistent with this study, and no clinically significant differences were observed in the safety outcomes in both studies.…”
Section: Discussionmentioning
confidence: 94%